2017
DOI: 10.1108/jmd-12-2016-0282
|View full text |Cite
|
Sign up to set email alerts
|

Women’s glass ceiling beliefs predict work engagement and burnout

Abstract: Purpose The purpose of this paper is to examine the relationship between glass ceiling beliefs, work engagement, and burnout. Design/methodology/approach A research model was developed based on the constructs from the Career Path Survey (CPS) and a literature review of research related to work engagement and burnout. Data from a cross-sectional study of 467 female employees from banks in India were collated and empirically tested, using structural equation modeling. Findings Denial and resilience were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
0
14
1
1
Order By: Relevance
“…The result of this study also revealed that there was no correlation between burnout and work engagement. While this result is supported by the previous finding (Hikmatullah, 2016), the result seems to be in contrary with the growing body of evidence, which suggests a negative correlation between burnout and work engagement (Balasubramanian & Lathabhavan, 2017;Christianty & Widhianingtanti, 2016;Fragoso et al, 2016;Hakanen, Bakker, & Schaufeli, 2006;Hakanen, Seppala, & Peeters, 2017;Maricutoiu, Sulea, & Lancu, 2017;Schaufeli, Bakker, & Van Rhenen, 2009;Sonnentag, 2017;Van Steenbergen, Van Der Ven, Peeters, & Waris, 2017).…”
Section: Discussioncontrasting
confidence: 70%
“…The result of this study also revealed that there was no correlation between burnout and work engagement. While this result is supported by the previous finding (Hikmatullah, 2016), the result seems to be in contrary with the growing body of evidence, which suggests a negative correlation between burnout and work engagement (Balasubramanian & Lathabhavan, 2017;Christianty & Widhianingtanti, 2016;Fragoso et al, 2016;Hakanen, Bakker, & Schaufeli, 2006;Hakanen, Seppala, & Peeters, 2017;Maricutoiu, Sulea, & Lancu, 2017;Schaufeli, Bakker, & Van Rhenen, 2009;Sonnentag, 2017;Van Steenbergen, Van Der Ven, Peeters, & Waris, 2017).…”
Section: Discussioncontrasting
confidence: 70%
“…To test the collected data statistically, initially, the data were coded and analysed using ‘Statistical Package for Social Sciences’ (SPSS 23.0 version). Further, one-sample t -test and multiple regression analysis were applied with a statistical significance level set at p <0.05 (Balasubramanian & Lathabhavan, 2017; Saleem, Rafiq, & Yusaf, 2017) to test the hypotheses formulated.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have explained the relationship and impact of glass ceiling on the level of engagement and suggested that the women employees receive differential treatment at their workplace, and their perception of gender discrimination negatively affects the level of their engagement towards work (Kim, 2015; Messarra, 2014; Sia, Sahoo, & Duari, 2015). Balasubramanian and Lathabhavan (2017) identified the relationship between glass ceiling beliefs (denial, resilience, resignation and acceptance) and work engagement among female employees and revealed positive association between glass ceiling beliefs (denial and resilience) and work engagement, while glass ceiling beliefs in terms of resignation and acceptance showed a negative relationship with work engagement. Ronald, Mustafa, and Lisa (2010) studied the relation between organizational practices (career barriers, equal treatment, male standards, negative attitudes towards women and support), women’s work attitudes, satisfaction level, work engagement and psychological well-being, and revealed that since the women experienced supportive organizational practices, they were highly engaged, satisfied (in terms of job and career) and portrayed high psychological well-being.…”
Section: Review Of Literature and Hypotheses Formulationmentioning
confidence: 93%
“…overcoming barriers that companies and women themselves put in the way" (Barsh and Yee, 2012). This, in the context of the factors that have been established (Balasubramanian and Lathabhavan, 2017;Bruckmüller et al, 2014;Holton, 2015;Eagly et al, 2007; as barriers to womens' career growth, necessitates a focus on programs at the university/ IHE that will prepare aspiring young women to achieve success in their respective careers paths. Real-life stories and experiences can pave the way to a positive attitude and selfawareness (Broadbridge, 2016), thereby drawing the right kind of understanding toward Denial and Resilience.…”
Section: Discussionmentioning
confidence: 99%